Lung function trajectories and bronchial hyperresponsiveness during childhood following severe RSV bronchiolitis in infancy. Issue 3 (6th November 2020) - Kitcharoensakkul, Maleewan; Bacharier, Leonard B.; Schweiger, Toni L.; Wilson, Brad; Goss, Charles W; Lew, Daphne; Schechtman, Kenneth B.; Castro, Mario
Abstract: Background: Children with severe respiratory syncytial virus (RSV) bronchiolitis in infancy have increased risks of asthma and reduced lung function in later life. There are limited studies on the longitudinal changes of lung function and bronchial hyperreactivity from early to late childhood in infants hospitalized for RSV bronchiolitis. Methods: In a prospective cohort of 206 children with their first episode of RSV‐confirmed bronchiolitis in the first year of life, 122 had spirometry performed at least twice between 5‐16 years of age. Methacholine bronchoprovocation was available in 127 and 79 children at 7 and 12 years of age, respectively. Longitudinal changes in FEV1, FVC, and FEV1 /FVC z‐scores and methacholine PC20 were analyzed. Results: 55% of the study cohort (N = 122) were male, and 55% were Caucasian. During follow‐up, longitudinal changes in z‐scores for pre‐ and post‐bronchodilator FEV1 ( P  < .0001) FVC ( P  < .0001) and FEV1 /FVC ( P  < .0001 for pre‐ and 0.007 for post‐bronchodilator) from age 5 to 10‐16 years were observed. Declined lung function in late childhood was significantly associated with gender, physician diagnosis of asthma, and allergic sensitization. PC20 geometric mean increased from 0.28 mg/mL at 7 years to 0.53 mg/mL at 12 years of age, and the frequency of abnormal bronchial hyperreactivity decreased from 96% to 78% ( P  = .0003). Conclusions: Following severe RSV bronchiolitis, there appear to be significant longitudinal changes in pre‐ and post‐bronchodilator lung function during childhood. The study has several limitations including significant dropouts and the lack of a control group and post‐bronchodilator measurements. Bronchial hyperreactivity is common in children following severe RSV bronchiolitis; however, it appears to decrease as they enter late childhood.